Radial forearm flaps as durable soft tissue coverage for local nationals being treated in the field hospital setting. Issue 1 (1st March 2013) - Hanna, KH; Jeffery, SLA
Abstract : The current conflict in Afghanistan has seen the increasing use of Improvised Explosive Devices (IED) in insurgency attacks. In addition to the coalition forces killed and injured from these devices, local national civilians are also injured. Injuries often include amputations, open fractures and large areas of skin affected by fragmentation. Local national access to long-term care after an IED injury is limited, and often when the patient leaves a coalition hospital this concludes the care the patient will receive. Definitive, durable treatment options are needed for these patients. In the IED-injured patient with open extremity wounds and open metacarpal fractures, pedicled radial forearm flaps offer a suitable soft tissue coverage option. Four cases are reported on IED- injured Afghan patients treated at a Role 3 hospital facility.